HYPERTENSION: A GLOBAL HEALTH CHALLENGE (Лучшие интеллектуальные исследования, 2025)
Hypertension, also known as high blood pressure, is a chronic medical condition where the blood pressure in the arteries is persistently elevated. It is often called the “silent killer” because it typically has no symptoms until significant organ damage occurs. According to the World Health Organization (WHO), hypertension affects more than 1.28 billion adults worldwide, and nearly 46% of adults with hypertension are unaware they have the condition.